2015
DOI: 10.1007/s10916-015-0287-2
|View full text |Cite
|
Sign up to set email alerts
|

A Context-Aware Interactive Health Care System Based on Ontology and Fuzzy Inference

Abstract: In the present society, most families are double-income families, and as the long-term care is seriously short of manpower, it contributes to the rapid development of tele-homecare equipment, and the smart home care system gradually emerges, which assists the elderly or patients with chronic diseases in daily life. This study aims at interaction between persons under care and the system in various living spaces, as based on motion-sensing interaction, and the context-aware smart home care system is proposed. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…Such type of shortened and concise data helps the medical director to know about the patient without any risk and what type of vaccine or medicine should be developed for certain diseases. Eventually, the data stored and updated records are sending to the fog data service 23 Data redundancy …”
Section: Proposed Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Such type of shortened and concise data helps the medical director to know about the patient without any risk and what type of vaccine or medicine should be developed for certain diseases. Eventually, the data stored and updated records are sending to the fog data service 23 Data redundancy …”
Section: Proposed Systemmentioning
confidence: 99%
“…In technological terms, the IoT refers to an air global neural network that communicates and interacts with environments, numerous machines, and objects to generate a huge amount of data. Thus, the generated data employ processing and controlling the things thereby portraying the life of humans more conveniently 23 . In the past few years, the problem based on global aging has created a troublesome errand and, in some cases, the elderly are subjected to high risk and even death.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, with the advance of ontology, related studies have revealed that ontologybased knowledge services have been developed in different areas, including personalized medicine [19], e-government [20], medicine [21,22], smart homes [23], the digital library [24,25], and so on.…”
Section: Related Workmentioning
confidence: 99%
“…The home is not only a single unit but also a component of a neighborhood under centralized management. In [ 29 ], an interactive health care system is proposed, aiming at enabling interaction between persons under care and incorporating the system in various living spaces, as based on motion-sensing interactions. Accordingly, flexible interactive services should be provided by different service providers.…”
Section: Related Workmentioning
confidence: 99%